EXPLORADORES DEL CAOS, ESTRATEGAS DEL ABISMO. CARTOGRAFÍA DE LA CARA OCULTA DEL CINE ESPAÑOL CONTEMPORÁNEO - Agustín Rubio Alcover, (Fonseca, Journal of Communication, 2023)
The present article tries to plan the map of the alternative models of production arisen immediately after the crisis in the Spanish contemporary cinema.